Utilization of waste into eco-enzyme as organic fertilizer in Tanjung Jati Village, Muara Enim Regency - Tuty Emilia Agustina; Muhammad Faizal; Elda Melwita; Enggal Nurisman; Rabecha Maros Framita; Muhammad Taufik (University of Merdeka Malang, 2025)
Tanjung Jati Village, Muara Enim Regency, faces the problem of suboptimal management of household and agricultural organic waste. Organic waste such as fruit peels and vegetable scraps is generally thrown away without processing, thus polluting the environment and causing an unpleasant odor. To overcome this, training and mentoring were conducted on processing organic waste into eco-enzymes as liquid organic fertilizer (POC). This activity aims to improve community knowledge and skills in utilizing organic waste independently and sustainably. The training involved 30 participants from farmers, village officials, and residents, using lecture, discussion, and direct practice methods. The evaluation results showed an increase in participant knowledge of 84 percent, with an average pre-test score of 20.23 to 37.23 in the post-test. A total of 9 kg of organic waste was successfully processed into 30 liters of eco-enzyme, then dissolved into POC with a dose of 20 ml eco-enzyme: 1000 ml water, then applied to kale plants. The treatment plants showed an average increase in height of 26 percent and the number of leaves of 32 percent compared to the control. This activity has proven effective in supporting organic waste management, increasing household agricultural yields, and strengthening public awareness of environmentally friendly agriculture.